Comparison of land use regression and random forests models on estimating noise levels in five Canadian cities. (January 2020) - Liu, Ying; Goudreau, Sophie; Oiamo, Tor; Rainham, Daniel; Hatzopoulou, Marianne; Chen, Hong; Davies, Hugh; Tremblay, Mathieu; Johnson, James; Bockstael, Annelies; Leroux, Tony; Smargiassi, Audrey
Abstract: Chronic exposure to environment noise is associated with sleep disturbance and cardiovascular diseases. Assessment of population exposed to environmental noise is limited by a lack of routine noise sampling and is critical for controlling exposure and mitigating adverse health effects. Land use regression (LUR) model is newly applied in estimating environmental exposures to noise. Machine-learning approaches offer opportunities to improve the noise estimations from LUR model. In this study, we employed random forests (RF) model to estimate environmental noise levels in five Canadian cities and compared noise estimations between RF and LUR models. A total of 729 measurements and 33 built environment-related variables were used to estimate spatial variation in environmental noise at the global (multi-city) and local (individual city) scales. Leave one out cross-validation suggested that noise estimates derived from the RF global model explained a greater proportion of variation (R 2 : RF = 0.58, LUR = 0.47) with lower root mean squared errors (RF = 4.44 dB (A), LUR = 4.99 dB (A) ). The cross-validation also indicated the RF models had better general performance than the LUR models at the city scale. By applying the global models to estimate noise levels at the postal code level, we found noise levels were higher in Montreal and Longueuil than in other major Canadian cities. Graphical abstract: Image 1 Highlights: The RF model has higher accuracy than the LUR model at the local and global scales. People living in Montreal and Longueuil exposed to relatively high noise levels. The noise estimates were assigned to postal code areas for future health studies. Abstract : We demonstrated that the random forests models performed better than land use regression models for estimating spatial variation in noise levels.